Chaotropic effect of trifluoroacetic and perchloric acid on β-cyclodextrin inclusion complexation process with risperidone, olanzapine and their selected impurities - Djajić, Nevena; Krmar, Jovana; Malenović, Andjelija; Otašević, Biljana; Protić, Ana (Archives of Pharmacy, 2020)
Effective method development together with method`s eco-friendly character are gaining importance in drug analyses nowadays. One of the strategies often applied to improve the efficacy of separation methods, especially in the case of basic ionizable analytes is adding chaotropic salts into the mobile phases. Moreover, the development of the green liquid chromatography method could also be achieved with certain mobile phase additives such as cyclodextrin (CD). The study aims to investigate whether adding chaotropic agents could improve the complexation process by disrupting the analytes’ water solvation shell. The model mixture consisted of risperidone, olanzapine, and their related impurities. Method development was aided with experimental design methodology, while optimal separation conditions were selected using Derringer’s desirability function. Mathematical models obtained for each of the examined responses enabled the explanation of the single and simultaneous influence of β-CD concentration, chaotropic agents type, and content, as well as the content of acetonitrile in the mobile phase. Retention factors appeared to be the most influenced by acetonitrile content in the mobile phase. The type of chaotropic agent as well as its concentration lead to retention prolongation, but if acetonitrile content in the mobile phase is high, the effect of chaotropic agent becomes negligible. Interaction between analyte and β-CD are relatively weak in comparison to the interaction of analyte form with either chaotropic agent or acetonitrile. Interaction leading to complexation are outperformed by other analyte related interactions in this complicated system, so complexation based retention reduction is not fully exposed. However, increasing β-CD concentration shows a positive effect on the resolution between critical peak pairs. Optimal separation conditions were selected based on 3D plots of Derringer’s desirability function. For olanzapine and its impurity, they included the following: acetonitrile content 16% (v/v), trifluoroacetic acid as a chaotropic agent with 0.95% (v/v) content, and 9 mM β-CD concentration. Further, optimal separation conditions for risperidone and its impurity were 25% (v/v) acetonitrile content in the mobile phase, trifluoroacetic acid as chaotrope agent with 0.27% (v/v) content and 5mM β-CD concentration.